2020
DOI: 10.1186/s12885-020-07166-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating different adoption scenarios for TIL-therapy and the influence on its (early) cost-effectiveness

Abstract: Background: Treatment with tumor-Infiltrating Lymphocytes (TIL) is an innovative therapy for advanced melanoma with promising clinical phase I/II study results and likely beneficial cost-effectiveness. As a randomized controlled trial on the effectiveness of TIL therapy in advanced melanoma compared to ipilimumab is still ongoing, adoption of TIL therapy by the field is confronted with uncertainty. To deal with this, scenario drafting can be used to identify potential barriers and enables the subsequent antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…The key limitation of this study was our reliance on publicly available data that may not reflect current clinical and tanning practices. While robust estimates for model input values could be identified in the published literature, this was not true for costs and clinical effectiveness of current diagnosis, treatment and monitoring options for patients with melanoma 35 . Advanced melanoma treatments have increased dramatically in the last 10 years and adjuvant treatment of stage 3 melanoma has been approved, which suggests that our base‐case values are underestimated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The key limitation of this study was our reliance on publicly available data that may not reflect current clinical and tanning practices. While robust estimates for model input values could be identified in the published literature, this was not true for costs and clinical effectiveness of current diagnosis, treatment and monitoring options for patients with melanoma 35 . Advanced melanoma treatments have increased dramatically in the last 10 years and adjuvant treatment of stage 3 melanoma has been approved, which suggests that our base‐case values are underestimated.…”
Section: Discussionmentioning
confidence: 97%
“…While robust estimates for model input values could be identified in the published literature, this was not true for costs and clinical effectiveness of current diagnosis, treatment and monitoring options for patients with melanoma. 35 Advanced melanoma treatments have increased dramatically in the last 10 years and adjuvant treatment of stage 3 melanoma has been approved, which suggests that our base-case values are underestimated. Clinical trials are under way in patients with stage 2 disease, a much larger patient population than stages 3 or 4.…”
Section: Discussionmentioning
confidence: 99%
“…The ex vivo TIL expansion protocol is labor-intensive and the requirement to use fresh TIL products for infusion impose further restrictions on the implantation. Outsourcing TIL production to dedicated manufacturing centers is necessary to increase the cost-effectiveness and expand the availability of this therapy [ 124 ]. Iovance Biotherapeutics has established a centralized, high-throughput manufacturing facility for the production of cryopreserved TILs (brand named Lifleucel).…”
Section: The Future Of Til-actmentioning
confidence: 99%
“…Despite the fact that TIL-ACT has yet to be FDA approved for the treatment of solid malignancies, strong preclinical and clinical results support its potential in eliciting durable tumor regression. therapy [124]. Iovance Biotherapeutics has established a centralized, high-throughput manufacturing facility for the production of cryopreserved TILs (brand named Lifleucel).…”
Section: The Future Of Til-actmentioning
confidence: 99%
“…TIL-based ACT in combination with high-dose IL-2 have been shown to be an effective clinical strategy in MM patients, and to a lesser extent, in other tumors. Although many issues remain to be addressed, especially regarding the relatively long generation process and the requirement for GMP facilities and trained personnel, the early-treatment costs are considerably lower than those of anti-CTLA4 mAb in MM ( 85 ). Given than TILs are naturally infiltrating cells, they can also serve as biomarker to predict the clinical efficacy of immunotherapies enhancing antitumor adaptive responses ( 86 ) Interestingly, different approaches have recently demonstrated that during the ex vivo process necessary for TIL generation, these tumor-specific T cells can be efficiently genetically modified in order to enhance their cytotoxicity, tumor homing or to reduce T cell exhaustion.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%